Identifikasi Serangan Serangga Hama di Pertanaman Padi (Oryza Sativa L.) di Lahan Persawahan Tinggarjaya - Anjani, Agillia; Pribadi, Teguh; B, Ardiana Kartika (Proceedings Series on Physical & Formal Sciences, 2021)
Rice crops is included into the family of Graminae that produces seeds from China. Rice Plant is the crops that produce rice, consumed approximately by 90 % from the whole citizens of Indonesia as the main food. This study aims to identify indect pest attacks in rice plantations in Tinggarjaya rice fields. From the results of the research that has been carried out, various kinds of insect pests were found in the Tinggarjaya rice fields. The main pests found were brown planthopper (N. Iguens), rice bug (Leptocorixa acuta), green grasshopper (Oxya serville), ground bedbug (Scotinophara coarctata F.), seed fly (Atherigona exigua), false white pest (Nymphula depunctalis guene), and green grasshopper (Atractomorpha crenulata). Each pest a different population density. Not all pests can be found at every stage of rice plant growth. The largest pest population was found in the generative stage.